2020
DOI: 10.3390/ijms21030787
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Cannabinoids as a Promising Approach for Impairing Fibroblast Activation and Prostate Cancer Progression

Abstract: Endo-, phyto- and synthetic cannabinoids have been proposed as promising anti-cancer agents able to impair cancer cells’ behavior without affecting their non-transformed counterparts. However, cancer outcome depends not only on cancer cells’ activity, but also on the stromal cells, which coevolve with cancer cells to sustain tumor progression. Here, we show for the first time that cannabinoid treatment impairs the activation and the reactivity of cancer-associated fibroblasts (CAFs), the most represented strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…It was found that WIN could relieve breast cancer [ 7 ], prostate cancer [ 15 ], and gastric cancer [ 19 ] in mice and prolong their survival by 50%. In vitro experiments showed that WIN could induce death of prostate cancer cells, liver cancer cells, and other tumor cells [ 20 , 21 ]. WIN inhibited DNA synthesis in T3 lymphocytes of human blastocysts and rodents, as well as in the Lewis lung cancer cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that WIN could relieve breast cancer [ 7 ], prostate cancer [ 15 ], and gastric cancer [ 19 ] in mice and prolong their survival by 50%. In vitro experiments showed that WIN could induce death of prostate cancer cells, liver cancer cells, and other tumor cells [ 20 , 21 ]. WIN inhibited DNA synthesis in T3 lymphocytes of human blastocysts and rodents, as well as in the Lewis lung cancer cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, emerging evidence suggests that cannabinoids have a dual role in counteracting prostate cancer progression, as well as the proliferation of stromal cells in the prostate tumor microenvironment. In a recent study, Pietrovito et al [ 36 ] reported that the cannabinoid treatment of prostate cancer cells (LNCaP, PC3, and DU145) selectively impaired cell-survival, while at the same time regulating prostrate stromal fibroblast phenotypes under in vitro conditions. The authors further showed that the activity of the synthetic cannabinoid WIN 55-212-2 was mediated by the increased expression of CB2 receptors, which are normally downregulated in healthy prostate fibroblast cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors further showed that the activity of the synthetic cannabinoid WIN 55-212-2 was mediated by the increased expression of CB2 receptors, which are normally downregulated in healthy prostate fibroblast cells. The expression of both CB1 and CB2 receptors was elevated in LNCaP cells compared to PC3 and DU145 cells [ 36 ]. Similar results were also found by Roberto et al [ 46 ], who demonstrated that WIN55,212-2 substantially reduced cell proliferation, invasion, and migration, as well as inducing G0/G1 cell cycle arrest apoptosis, in a dose-dependent manner in cultured PC3, DU145, and LNCaP prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WIN 55,212-2 inhibited tumor proliferation in prostate cancer via CB2R [ 65 , 66 ] and in human BEL7402 hepatocellular carcinoma cells [ 67 ]. WIN 55,212-2 and CP 55-940 induced cell death in C6 (rat) and U373 (human) glioma tumour lines [ 68 ].…”
Section: Cannabinoid Ligandsmentioning
confidence: 99%